Optimization of Islamic Peer-to-Peer Lending for Micro and Small Enterprises (MSEs) After Pandemic of Covid-19 - Bella, Firsty Izzata (Universitas Muhammadiyah Surakarta, 2020)
Indonesia and the rest of the world are grieving over the Covid-19 pandemic from December 2019 to the present, besides, no body known when this pandemic will end. In addition to impacting global health, the economy also experience the effects. One of the sectors that most got the impact of Covid-19 was the Micro and Small Business Sector (MSE). This research applied descriptive qualitative method through literature study utilized from books, scientific journals and other sources as supporters. The data used is intended as support for the phenomenon that occurs in Indonesia. Finally, the researcher tried to propose a new scheme in the form of filing MSE financing in groups according to business categories through the Islamic peer-to-peer lending (P2P) platform to provide easy capital access for the enterprises after the Covid-19 pandemic.